Structural Damping in Sandwich Shells - Tuan, Ho Thien; Łukasiewicz, S. (Engineering Transactions, 1976)
The basic equations governing the motion of sandwich shells are derived through the use of a variational procedure. Structural damping is investigated in the case of a cylindrical sandwich shell with dissimilar facings, executing axially symmetric free vibrations. The concept of the complex modulus is used in order to describe the viscoelasticity of the core. The various frequency parameters of the shell and their associated damping parameters are obtained and analyzed with regard to the ratios of different layers thicknesses and other geometrical and physical properties of the sandwich shell. Curves obtained from numerical results are presented.